2020
DOI: 10.1177/0300060520924265
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on advanced renal cell carcinoma

Abstract: Renal cell carcinoma (RCC) is a malignant tumor and the third most common urinary disease. It was estimated that RCC affected over 350,000 individuals in 2013, and there are nearly 140,000 deaths annually due to this disease. The initial masses in RCC patients are mostly confined to a single organ. However, due to the metastatic spread of cancer cells through the circulatory system, more than 30% of RCC patients relapse after surgery. The appearance of distant metastases often means that patients enter the adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 53 publications
0
12
0
1
Order By: Relevance
“…[3] Although significant progress has been made in laparoscopic surgery or nephrectomy for RCC compared with the past, which can preserve renal function more completely and minimize cancer progress, However, studies have shown that up to 30% of patients will relapse after tumor resection. [4] At present, tumor stage and Fuhrman's pathological nuclear grading system are considered to be the most important prognostic factors of RCC, but even so, the improvement of prognosis can only focus on the prolongation of 5-year survival rate rather than the cure of tumor. Therefore, the correct identification of the recurrence and prognostic factors of RCC has always been the core issue of improving the survival time, which is very important for prolonging the survival time, dynamically monitoring the prognostic changes of patients, especially the prediction of cancer recurrence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Although significant progress has been made in laparoscopic surgery or nephrectomy for RCC compared with the past, which can preserve renal function more completely and minimize cancer progress, However, studies have shown that up to 30% of patients will relapse after tumor resection. [4] At present, tumor stage and Fuhrman's pathological nuclear grading system are considered to be the most important prognostic factors of RCC, but even so, the improvement of prognosis can only focus on the prolongation of 5-year survival rate rather than the cure of tumor. Therefore, the correct identification of the recurrence and prognostic factors of RCC has always been the core issue of improving the survival time, which is very important for prolonging the survival time, dynamically monitoring the prognostic changes of patients, especially the prediction of cancer recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] Although significant progress has been made in laparoscopic surgery or nephrectomy for RCC compared with the past, which can preserve renal function more completely and minimize cancer progress, However, studies have shown that up to 30% of patients will relapse after tumor resection. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…У пациентов с почечно-клеточным раком часто возникают связанные с заболеванием симптомы, в том числе боль в поясничной области, гематурия, боль в костях, кашель, пальпируемая опухоль в животе и проявления паранеопластического синдрома, которые могут снижать качество жизни больных [9,10]. Кроме этого, известно, что некоторые нежелательные явления, такие как кожная сыпь, тошнота, диарея, усталость и мышечно-скелетная боль, на фоне терапии ингибиторами киназ и иммунотерапии могут ухудшать качество жизни [11][12][13][14][15].…”
Section: Introductionunclassified
“…A prior study reported that patients with fasting blood glucose levels higher than 7.8 mmol/l have a 25% higher chance of dying from tumors than those with a fasting blood glucose level lower than 5.6 mmol/l [4]. The renal cancer ranks the third in urinary system tumors, and its incidence has shown a rising tend [5]. A previous study revealed that the incidence and mortality of diabetes patients with renal cancer increased by 47% and 43% [6] versus those without diabetes.…”
Section: Introductionmentioning
confidence: 99%